Role of Education and Training on Income in Different Regions of Latvia - Sloka, Biruta; Tora, Ginta; Buligina, Ilze; Dzelme, Juris (My University, 2019)
Latvia is often critisised by international institutions on rising gap for income differences in several social groups. This current research is devoted to analyse of role of education and training on income level. Research methods used: scientific publications and previous conducted research analysis, analysis of EU-SILC data on differences in income depending from education level, from regions and from territory (urban/rural), interviews of regional authorities on life-long training arrangements and applications in regions with lower income level. Data analysis methods: descriptive statistics (indicators of central tendency or location, indicators of variability), cross-tabulations of household income by regions, by education level, by territories, testing of statistical hypotheses on differences of arithmetic means by t-test, by analysis of variance (ANOVA) for significance of income differences by regions and by education level. Results of analysis has indicated that several innovative approaches could be applied to find best solutions for income difference decrease and increase of overall satisfaction with life.
Keywords: Education and training; EU-SILC; Income differences; Regions; Welfare; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::SOCIAL SCIENCES::Business and economics